The long road to Pokemon Black and White. - Noble, McKinley (Gamepro)
In an exclusive interview from their Tokyo headquarters, Game Freak cofounders Junichi Masuda and Ken Sugimori describe the challenges of video-game development and their takes on the growth and future of Pokemon.